Impact of supradiaphragmatic lymphadenectomy on the survival of patients in stage IVB ovarian cancer with thoracic lymph node metastasis - Park, Soo Jin; Na, Kwon Joong; Lee, Maria; Park, In Kyu; Chung, Hyun Hoon; Kang, Chang Hyun; Kim, Jae-Weon; Park, Noh Hyun; Kim, Young-Tae; Song, Yong Sang; Park, Samina; Kim, Hee Seung (Frontiers in Oncology, 2023)
To evaluate the survival impact of supradiaphragmatic lymphadenectomy as part of debulking surgery in stage IVB ovarian cancer with thoracic lymph node metastasis (LNM).We retrospectively enrolled patients diagnosed with stage IVB ovarian, fallopian or primary peritoneal cancer between 2010 and 2020, carrying cardiophrenic, parasternal, anterior mediastinal or supraclavicular lymph nodes ≥5 mm on axial chest computed tomography. All tumors were classified into the abdominal (abdominal tumors and cardiophrenic lymph nodes) and This is a provisional file, not the final typeset article supradiaphragmatic (parasternal, anterior mediastinal or supraclavicular lymph nodes) categories depending on the area involved. Residual tumours were classified into <5 vs ≥5 mm in the abdominal and supradiaphragmatic areas. Based on the site of recurrence, they were divided into abdominal, supradiaphragmatic and other areas.Results: A total of 120 patients underwent primary debulking surgery (PDS, n=68) and interval debulking surgery after neoadjuvant chemotherapy (IDS/NAC, n=53). Residual tumors in the supradiaphragmatic area ≥5 mm adversely affected progression-free survival (PFS) and overall survival (OS) with marginal significance after PDS despite the lack of effect on survival after IDS/NAC (adjusted hazard ratios [HRs], 6.478 and 6.370; 95% confidence intervals [CIs], 2. 224-18.864 and 0.953-42.598). Further, the size of residual tumors in the abdominal area measuring ≥5 mm diminished OS after IDS/NAC (adjusted HR, 9.330; 95% CIs, 1.386-62.800).Conclusions: Supradiaphragmatic lymphadenectomy during PDS may improve survival in patients diagnosed with stage IVB ovarian cancer manifesting thoracic LNM. Further, suboptimal debulking surgery in the abdominal area may be associated with poor OS after IDS/NAC.